2013
DOI: 10.1155/2013/834295
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus Vulgaris and Infections: A Retrospective Study on 155 Patients

Abstract: Background. Autoimmune process and immunosuppressive therapy of pemphigus vulgaris would predispose the patients to infections. Aim. We aimed to study the prevalence of infection and pathogenic agents in pemphigus vulgaris patients admitted to dermatology service. Material and methods. This retrospective study was conducted on 155 pemphigus vulgaris patients (68 males, 87 females) admitted to dermatology service between 2009 and 2011. In this study, the diagnosis of pemphigus vulgaris was confirmed by light mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
49
1
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 21 publications
(23 reference statements)
13
49
1
3
Order By: Relevance
“…They could not detect these viruses in any of these patients [11]. Another retrospective study by Esmaili et al in 2013 on 155 patients of pemphigus 9.68% were found to have localized herpes simplex infection [12]. In a recent study in 2013 by Mahnaz Banihashmi et al 30 diagnosed cases of pemphigus were analysed for presence of HSV1, EBV, HSV2 and HHV8 by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 97%
“…They could not detect these viruses in any of these patients [11]. Another retrospective study by Esmaili et al in 2013 on 155 patients of pemphigus 9.68% were found to have localized herpes simplex infection [12]. In a recent study in 2013 by Mahnaz Banihashmi et al 30 diagnosed cases of pemphigus were analysed for presence of HSV1, EBV, HSV2 and HHV8 by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 97%
“…Šios ligos prognozė iki gydymo eros sisteminiais kortikosteroidais (KS) ir imunosupresiniais vaistais daž-niausiai buvo bloga. Gausios akantolizinės pūslės ir išpli-tusios šlapiuojančios erozijos odoje ir gleivinėse, skysčių ir proteinų netekimas, elektrolitų disbalansas dėl odos barjero pažeidimo, antrinė bakterinė, virusinė ar grybelinė infekcijos buvo letalios baigties priežastys [1,2]. Pemphigus diagnostika sudėtinga, dažnai -pavėluota, ypač kai bėrimai prasideda tik burnos gleivinėje.…”
Section: įVadasunclassified
“…Literatūros duomenimis, sergant pemphigus, šių infekcijų dažnis siekia 60 -68 proc. Neretai šios infekcijos sukelia sunkias komplikacijas ir gali lemti fatalinę baigtį [2]. Antrinių infekcijų profilaktikai skiriamos vonios su antiseptikais, vietiniai antiseptikai ir antibiotikai, antivirusinis gydymas herpetinės infekcijos profilaktikai.…”
Section: Lakštinė Pūslinėunclassified
“…5 Hospitalization in addition to corticosteroid therapy (with or without adjuvant immunosuppressive agents) would predispose the pemphigus patients to infection, with skin infection as one of the most frequently acquired. 4 This is a case report of nosocomial infection manifested as erysipelas in a patient under immunosuppressive therapy.…”
Section: Introductionmentioning
confidence: 97%
“…2 The etiology of SSTIs may be normal host flora transferred through a break in the barrier, such as instrumentation (eg, needles), that could permit the entry of normal skin flora and indigenous flora from the instrument of penetration. 3 Esmaili et al 4 reported that S. aureus responsible for 93,7% of skin infections in pemphigus patients.…”
Section: Introductionmentioning
confidence: 99%